Restoration of formation processes of dolomite reservoirs based on laser U-Pb dating: A case study of Ordovician Majiagou Formation, Ordos Basin, NW China - Jingao ZHOU; Zhou YU; Dongxu WU; Junfeng REN; Daofeng ZHANG; Shaoyi WANG; Chen YIN; Yuxin LIU (Petroleum Exploration and Development, 2022)
To address the issue of non-unique interpretation of dolomite reservoir diagenetic and porosity evolution in the previous qualitative or semi-quantitative studies, we investigate two dolomite reservoir types, i.e. weathering-crust karstic reservoirs and mound-beach reservoirs, in the Ordovician Majiagou Formation, Ordos Basin by using in-situ laser ablation U-Pb dating as well as carbon and oxygen isotopic composition analysis. The results show that: (1) According to the dating of 8 reservoir samples, the Majiagou Formation experienced 5 diagenetic stages (Stage 1: deposition of matrix dolomite or penecontemporaneous dolomitization, in 444.0–494.0 Ma; Stage 2: dogtooth- or blade-shaped dolomite cementation, in 440.0–467.0 Ma; Stage 3: dolomitic silt filling, in 316.5–381.0 Ma; Stage 4: crystalline dolomite filling, in 354.0 Ma; Stage 5: crystalline calcite filling, in 292.7–319.0 Ma). (2) Supra-salt weathering-crust karstic dolomite reservoirs went through several diagenetic processes including penecontemporaneous dolomitization, compaction, weathering-crust karstification, packing, and rupturing in succession. Gypsum mold pores formed in the phase of hypergenic karstification and were filled with such minerals as dolomitic silts and calcites, and thus the porosity decreased from 10%–40% to 3%–8%. (3) Sub-salt mound-beach dolomite reservoirs went through the diagenetic processes including penecontemporaneous dolomitization, compaction, subsea cementation, penecontemporaneous corrosion, infiltration backflow dolomitization, packing, and rupturing. The porosity of reservoirs was originally 10%–30%, decreased to 0–6% due to seawater cementation, rose back to 5%–15% owing to penecontemporaneous corrosion, and finally declined to 2%–6% as a result of crystalline dolomites and calcites packing. The above methodology for the restoration of dolomitization and porosity evolution may be helpful for the restoration of porosity evolution in other basins or series of strata.